Induction of tumor antigen-specific immunity in vivo by a novel vaccinia vector encoding safety-modified simian virus 40 T antigen - Xie, Y C; Hwang, C; Overwijk, W; Zeng, Z; Eng, M H; Mulé, J J; Imperiale, M J; Restifo, N P; Sanda, M G (JNCI : Journal of the National Cancer Institute, 1999)
Evidence that simian virus 40 (SV40) is associated with human mesotheliomas, osteosarcomas, and brain tumors suggests that a recombinant vaccine directed against lethal cancers expressing SV40 T antigen (Tag) could have clinical utility. To address this potential need, we designed a novel vaccinia virus construct that encodes an SV40 Tag in which oncogenic domains were excluded and immunogenic domains were preserved. We named this recombinant construct vaccinia-encoding safety-modified SV40 Tag (vac-mTag). Purified vac-mTag was characterized by DNA sequencing, reverse transcription-coupled polymerase chain reaction, western blot analysis, and immunocytochemical techniques. Induction of Tag-specific immunity was examined by cytolytic T-cell assays, and the efficacy of vac-mTag in protecting animals against Tag-expressing tumors and in treating pre-established microscopic tumors was evaluated in vac-mTag-immunized BALB/c mice. The immune response elicited by vac-mTag in C57BL/6 and BALB/c mice included an SV40 Tag-specific cytolytic T-lymphocyte activity against syngeneic (identical genetic background) SV40 Tag-expressing tumor targets. Immunization of mice with a single dose of vac-mTag resulted in potent protection against subsequent challenge with a lethal mouse cancer expressing SV40 Tag. In addition, single-dose vac-mTag immunization coadministered with interleukin 2 produced a possible therapeutic effect against a preadministered microscopic (but lethal) burden of Tag-expressing tumor cells in vivo. vac-mTag induces an effective immune response in mice that is specific for a tumor-associated antigen. This response protects against a lethal tumor challenge and results in a possible therapeutic effect against Tag-expressing tumors in vivo. Thus, vac-mTag provides a new avenue for the development of therapies for human cancers thought to be associated with SV40.